Association between serum endothelin-1 level and major adverse cardiovascular events following percutaneous coronary intervention in stable coronary artery disease - Dian Herlusiatri Rahayu; Dyah Wulan Anggrahini; Anggoro Budi Hartopo (Published by Universitas Gadjah Mada, 2025)
Coronary artery disease (CAD) affects greatly the global population, exhibits high mortality and morbidity rates. Major adverse cardiovascular events (MACE), such as stroke, myocardial infarction, heart failure, and death, are the focus of research due to their significant contribution to morbidity and mortality in patients with CAD. Endothelin-1 is identified as a CAD prognostic indicator, especially for heart failure outcome. This study aimed to investigate the association between serum endothelin-1 level and MACE within 1 yr observation in patients with CAD underwent percutaneous coronary intervention (PCI). It was a retrospective cohort study where conducted at Dr. Sardjito General Hospital, Yogyakarta, Indonesia. Subjects were patients with stable CAD who underwent elective PCI. Baseline serum endothelin-1 level was measured by ELISA at the time of elective PCI procedure. The outcome was MACE, which consisted of heart failure, acute coronary syndrome, stroke, and cardiac death, occurred within 1 yr after elective PCI. The ROC curve was designed to determine serum endothelin-1 cut-off value to predict MACE. Sixty-three subjects were enrolled and the endothelin-1 level in serum samples was analyzed. Out of these, 11 (17.5%) experienced MACE within 1 yr post elective PCI. Serum endothelin-1 cut-off value was 1.932 pg/mL, which determined based on ROC curve. There was no significant association between serum endothelin-1 and MACE. There was a trend of higher incidence of MACE, in subjects with above-cut-off endothelin-1 level (≥1.932 pg/mL) (MACE incidence: 23.1% vs. 8.3%; p=0.181). Above-cut-off endothelin-1 level significantly associated with incidence of heart failure (100% vs. 0%; p=0.039) for 1 yr follow-up after elective PCI. Higher serum endothelin-1 level had a trend of higher incidence of 1-yr MACE in patients with stable CAD undergone elective PCI. Among 1-yr MACE, higher serum endothelin-1 associated with increased incidence of heart failure.